ANALISIS EFEKTIVITAS INSTALASI PENGOLAHAN AIR LIMBAH (IPAL) DI RUMAH SAKIT UMUM DAERAH KABUPATEN SUMEDANG DENGAN PARAMETER BOD, COD DAN TSS - Nur hayati; soleh apip (JURNAL TECHLINK, 2021)
Sumedang regional general hospital in the implementation of activities produces liquid waste which is if disposed directly to environment will cause water contamination and human health problems. The purpose of this study is to analyze the effectiveness of waste water treament plant performance in treating waste water based parameters BOD5, COD and TSS. The analysis of this study uses a T-Test statistical with SPSS software and also by calculating the efficiency of pollutants removal with using data before and after treatment to determine the effectiveness of waste water treament plant. Based on laboratory test result, the effluent concentration for BOD5, COD and TSS have fulfilled the standard discharge limit according to Ministry Of Environment and Forestry no.68/2016 and the chrom content in waste sludge has fulfilled with the standard discharge limit according to Ministry Of Environment and Forestry no.05/2014. The T-test interpretation result showed that the BOD5 and COD parameters have significant difference between the data before treatment and after treatment. Based on laboratory test result in November 2020, the efficiency of removal pollutanst for TSS 94.59%, BOD5 78.78% and COD 73.23%.